The Current Status of Social Isolation and the Caregiver Compassion Fatigue in Elderly COPD Patients - Liu H; Zhao Z; Shi H; Yang R (Clinical Interventions in Aging, 2025)
Hong Shi,1 Zhen Zhao,1,* Huijun Liu,2,* Rujie Yang3 1Department of Clinical Nursing, Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 2Department of Emergency treatment, West China Hospital of Sichuan University, Chengdu, People’s Republic of China; 3The Ninth People’s Hospital affiliated to Shanghai Jiao Tong University School of Medicine, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rujie Yang, The Ninth People’s Hospital affiliated to Shanghai Jiao Tong University School of Medicine, No. 639, Manufacturing Bureau Road, Huangpu District, Shanghai, 200000, People’s Republic of China, Tel +86-13651898821, Email jjflowerhony@163.comBackground: Chronic obstructive pulmonary disease (COPD) significantly affects elderly individuals, often leading to social isolation and impacting quality of life. Family caregivers play a crucial role but may experience compassion fatigue (CF), potentially exacerbating patient outcomes. This study investigates social isolation in elderly COPD patients and examines the impact of caregiver compassion fatigue.Methods: We conducted a retrospective analysis of 200 elderly COPD patients from January 2018 to December 2022 at West China Hospital of Sichuan University. Participants were divided into poor prognosis (n = 109) and good prognosis (n = 91) groups based on outcomes within 90 days of admission. Caregiver compassion fatigue was assessed using the Professional Quality of Life Scale (ProQOL), categorizing patients into low (n = 125) and high (n = 75) caregiver fatigue groups. Social isolation was measured using the Generalized Alienation Scale (GAS) and the Multidimensional Scale of Perceived Social Support (MSPSS). Patient outcomes included pulmonary function tests, the 6-Minute Walk Test (6MWT), and psychological assessments using the Hospital Anxiety and Depression Scale (HADS), Connor-Davidson Resilience Scale (CD-RISC), and the Satisfaction with Life Scale (SWLS).Results: No significant demographic differences were observed between GP and PP groups. The PP group exhibited higher GAS scores (P = 0.017) and lower MSPSS scores (P = 0.045), indicating greater social isolation. Caregivers of PP patients reported higher compassion fatigue and burnout levels (P = 0.007; P = 0.003). Elevated caregiver compassion fatigue correlated with poorer patient outcomes, including decreased exercise tolerance (P = 0.021) and increased anxiety and depression (P = 0.008 and P = 0.045, respectively). Lower resilience and life satisfaction scores were observed in patients with caregivers experiencing high compassion fatigue, highlighting the impact on psychological well-being.Conclusion: Elderly COPD patients often experience significant social isolation, exacerbated by high levels of caregiver compassion fatigue.Keywords: chronic obstructive pulmonary disease, social isolation, compassion fatigue, caregiver burnout, elderly patients, psychosocial outcomes